Buying and Selling Gas LPG 3 Kg According to Law Number 8 of 1999 and Sharia: Case Study in Bengkalis District - Zulfikar Hasan; Yuni Dhea Utari; Irlina Dewi (UIN Kiai Haji Achmad Siddiq Jember, 2023)
This analysis examined the phenomenon in Bengkalis District relating to purchasing 3 kg LPG gas. Researchers analyzed following Law No. 8 of 1999 concerning Consumer Protection Against the sale and purchase of 3 kg LPG gas. In addition, the research tries to analyze the prohibition of ihtikar for staples. Many problems arise because a business actor, one of which is a business actor, reduces the contents volume of gas liquefied petroleum gas (LPG) by 3 kg. Constraints in implementing the protection of the Kosumen against the sale and purchase of gas in Bengkalis Sub-Electricity, consumers need help getting 3 kg LPG gas due to some obstacles. There are still many consumers who feel that they live in injustice carried out by business actors to sell their merchandise because many business actors are looking for profit from consumers. This study also exposed the Ihtikar prohibition for basic goods. This study uses a qualitative method based on Law No. 8 of 1999 and explores, according to Muslim scholars, the ban on the accumulation of goods